Unthinking Mastery Dehumanism and Decolonial Entanglements - Singh, Juliette (Duke University Press, 2017)
In UNTHINKING MASTERY Julietta Singh demonstrates how pervasive the concept of mastery has been to modern politics, even to anti-colonial thought, which rejects forms of political domination and subjection. Anti-colonial discourse, Singh argues, has sought to recuperate the humanity of the colonized in ways that remain bound to masterful formulations of subjectivity. Drawing on postcolonial theory, queer theory, new materialism, and animal studies, Singh analyzes critiques of mastery across anti-colonial discourse to explore how modern formulations of decolonization that were explicitly pitched against colonial mastery continuously rehearse "other" forms of mastery in order to exceed it. Singh's goal isn't to discipline important figures from anti-colonial politics or the contemporary intellectual left, but rather to take seriously the messiness of our political strategies in the hope of deriving un-masterful styles of being.